STUDI PERMODELAN RUMAH ACEH DENGAN PEMAKAIAN BAJA RINGAN SEBAGAI ALTERNATIF BAHAN KONSTRUKSI: Aceh House Modeling Study Using Light Steel as An Alternative Construction Material - Satria, Andrisman; Rahman, Aulia (Jurnal Rekayasa Infrastruktur HEXAGON, 2023)
The traditional Acehnese house, known as "rumoh Aceh," is a precious cultural heritage that has become an architectural icon of the region. However, their vulnerability to earthquakes and tsunamis has prompted research into the use of alternative construction materials to improve the seismic resistance of Acehnese houses. This study aims to assess the comparison of internal forces occurring in Acehnese houses with mild steel construction as an alternative construction material, using the response spectrum method. The study adopted a quantitative approach and sampled Acehnese houses covering a wide range of types and ages. Data on house characteristics, including design, construction materials, Furthermore, computer models of Aceh houses with mild steel construction and conventional Aceh houses were analysed using the response spectrum method. The results showed that Acehnese houses with C75 mild steel construction showed that the internal forces obtained gave unsafe design results with the single cross-section so that larger dimensional changes to the double cross-section were required. Spectrum response analysis provides a better understanding of how mild steel construction can reduce the risk of earthquake damage. The findings indicate that the use of mild steel as an alternative construction material in Acehnese houses is a viable option to improve earthquake resistance, preserve their cultural heritage, while protecting lives and property.